Decision Support System For Placement Of Honorary Employees Based On Work Competence Using Analytical Hierarchy Process Method - Martin Heri Gosen Simanungkalit; Roy Fanry Siahaan (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
In civil service law knowledge, what distinguishes the status of one employee from another can be seen from the system of appointment to serve in public services. There are two types of employment status in Indonesia: civil servants, now known as State Civil Apparatus (ASN), and contract or honorary employees. Honorary staff is people who are appointed by staffing officers or other officials in the government to carry out certain tasks in government agencies. A Decision Support System (DSS) is a way of organizing information (involving the use of databases) that is intended to be used in making decisions. Analytical Hierarchy Process (AHP) is a method for solving a complex situation that is not structured into several components in a hierarchical arrangement, by assigning a subjective value to the relative importance of each variable, and determining which variable has the highest priority in influencing the outcome of the situation. With the help of a decision support system in managing the placement of temporary workers by implementing the Analytical Hierarchy Process (AHP), it can work well. The results of the application of the Analytical Hierarchy Process (AHP) method in the placement of temporary workers with 6 criteria against 3 data samples were 0,546; 0.315 and 0.314 With the help of a decision support system in managing the placement of temporary workers by implementing the Analytical Hierarchy Process (AHP) it can work well. The results of the application of the Analytical Hierarchy Process (AHP) method in the placement of temporary workers with 6 criteria against 3 data samples were 0,546; 0.315 and 0.314 With the help of a decision support system in managing the placement of temporary workers by implementing the Analytical Hierarchy Process (AHP) it can work well. The results of the application of the Analytical Hierarchy Process (AHP) method in the placement of temporary workers with 6 criteria against 3 data samples were 0,546; 0.315 and 0.314